2019
DOI: 10.1128/jvi.01474-18
|View full text |Cite
|
Sign up to set email alerts
|

αvβ3 Integrin Is Required for Efficient Infection of Epithelial Cells with Human Adenovirus Type 26

Abstract: Human adenoviruses (HAdVs) are being explored as vectors for gene transfer and vaccination. Human adenovirus type 26 (HAdV26), which belongs to the largest subgroup of adenoviruses, species D, has a short fiber and a so-far-unknown natural tropism. Due to its low seroprevalence, HAdV26 has been considered a promising vector for the development of vaccines. Despite the fact that thein vivosafety and immunogenicity of HAdV26 have been extensively studied, the basic biology of the virus with regard to receptor us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 45 publications
1
40
0
Order By: Relevance
“…Oncolytic virus (OV) therapy is a novel and promising therapeutic approach for tumors that involves selectively infecting and killing tumor cells. Prior research studies demonstrated that αvβ3 integrin and nectin-1 are required for efficient infection of cells by herpesvirus and adenovirus, respectively 7,8 , and the underlying mechanism may involve OV-induced cell destruction by cancerspecific genetic alteration, as well as sequential virus release and viral infection. It was first reported that tumors could be inhibited or shrunk in patients with cervical cancer and rabies virus positivity 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Oncolytic virus (OV) therapy is a novel and promising therapeutic approach for tumors that involves selectively infecting and killing tumor cells. Prior research studies demonstrated that αvβ3 integrin and nectin-1 are required for efficient infection of cells by herpesvirus and adenovirus, respectively 7,8 , and the underlying mechanism may involve OV-induced cell destruction by cancerspecific genetic alteration, as well as sequential virus release and viral infection. It was first reported that tumors could be inhibited or shrunk in patients with cervical cancer and rabies virus positivity 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the primary cellular receptor usage for these species D Ads has not been fully determined and remains controversial in the literature. For example, some studies have suggested that Ad26 uses CD46 as a cellular receptor [5,16,22,23] while other studies challenge the utilization of CD46 and instead suggest CAR [37,38], αvβ3 integrin [39], scavenger receptor SR-A6 [40], sialic acid-bearing glycans [41], or another uncharacterized receptor as the primary receptor. Receptor usage for Ad48 also remains controversial [5,16,23,38,42] while receptor usage for Ad28 and Ad45 has not been explored in depth [20,23].…”
Section: Discussionmentioning
confidence: 99%
“…Ma and colleagues in 2018 reported that IRE1α act as an endoplasmic reticulum stress sensor, leading to increased expression of negative regulators of JAK/STAT, suppressor of cytokine signaling (SOCS)-1 and SOCS-3 in response to CoVs transmissible gastroenteritis virus. Therefore, IRE1α may be a novel target against COVID-19 and requiring further studies [ 126 ]. At the moment the present review is being written, it has not been reported targeting IRE1α to confirm its therapeutic effects in COVID-19 infection.…”
Section: Jak/stat Inhibitorsmentioning
confidence: 99%